Mass Transfer During Osmotic Dehydration of Chub Mackerel Cylinders in Ternary Solution - Checmarev, Gerardo (2014)
In the analysis, design and optimization of an osmotic dehydration process is important to know the kinetic of water loss and solutes gain. In this study, the mass transfer during osmotic dehydration of chub mackerel (Scomber japonicus) cylinders in ternary solution glycerol/salt/water was analyzed. The models of Zugarramurdi & Lupín and Azuara were used to describe mass transfer and to estimate equilibrium values. The radial effective diffusion coefficient was estimated using the analytical solution of Fick's second law. Diffusion coefficients were determined for a finite cylinder, for an infinite cylinder considering only the first term of the series and considering higher order terms of the series. The profiles of water and solutes during the osmotic dehydration were calculated by using the estimated water and solutes diffusivities. According to the results obtained, using three terms in the analytical solution of the Fick's second law is appropriate to determine the diffusion coefficients. The diffusion coefficient for infinite cylinder were 2.63×10-6, 4.11×10-6 and 4.25×10-6 cm2/s for water loss, salt and glycerol gain respectively. For a finite cylinder these values were 2.30×10-6, 3.67×10-6 and 3.78×10-6 cm2/s respectively. All the models proposed were in agreement with experimental data for solutes gain ((0.967<R2adj<0.986); (0.0016<RMSE<0.039) and (4.17<P<10.0)). The model based on the solution of Fick’s Law for an infinite cylinder with higher order terms was the best fit for water loss and solutes gain. The equilibrium values estimated with Azuara model agree with the experimental (0<relative error<9.8). Water and solute distributions as a function of time and location in the radial direction were plotted